Crystal structure, site selectivity, and electronic structure of layered chalcogenide LaOBiPbS3. (26th September 2017) - Mizuguchi, Y.; Hijikata, Y.; Abe, T.; Moriyoshi, C.; Kuroiwa, Y.; Goto, Y.; Miura, A.; Lee, S.; Torii, S.; Kamiyama, T.; Lee, C. H.; Ochi, M.; et al.
Abstract: We have investigated the crystal structure of LaOBiPbS3 using neutron diffraction and synchrotron X-ray diffraction. From structural refinements, we found that the two metal sites, occupied by Bi and Pb, were differently surrounded by the sulfur atoms. Calculated bond valence sum suggested that one metal site was nearly trivalent and the other was nearly divalent. Neutron diffraction also revealed site selectivity of Bi and Pb in the LaOBiPbS3 structure. These results suggested that the crystal structure of LaOBiPbS3 can be regarded as alternate stacks of the rock-salt–type Pb-rich sulfide layers and the LaOBiS2 -type Bi-rich layers. From band calculations for an ideal (LaOBiS2 )(PbS) system, we found that the S bands of the PbS layer were hybridized with the Bi bands of the BiS plane at around the Fermi energy, which resulted in the electronic characteristics different from that of LaOBiS2 . Stacking the rock-salt type sulfide (chalcogenide) layers and the BiS2 -based layered structure could be a new strategy to exploration of new BiS2 -based layered compounds, exotic two-dimensional electronic states, or novel functionality.